Social Capital Community in Conserving Sheets in Paloan Village Raden Sengah Temila Landak Regency - Khosmas Khosmas (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Humans cannot live apart from their surroundings. Environment for humans is one of the most important elements in their lives because all life necessities are available in it. Communities in and around forests have a high dependence on forests because forests are considered capable of meeting household needs in the form of food, shelter, traditional medicines and economic resources for the community. This study aims to find a relationship between social capital and the carrying capacity of the community in preserving Tembawang. This research was carried out based on exploratory and descriptive methods. Respondents studied were 136 people. Data analysis was carried out using a qualitative approach. Data collection techniques used include interviews, questionnaires, documentary studies, field observations. The conclusion of the research results is that the individual characteristics in this study are conditions that are inherent in an individual or someone. Community social capital in Tembawang management in Raden-Village Paloan Hamlet is good. Proactive actions in the Raden- Village Paloan Hamlet community are one of the important elements in social capital, namely the strong desire of group members not only to participate but always to find ways for their involvement in community activities. Based on the study, it can be suggested that the formation of a good social network in Tembawang conservation management efforts in Raden Village Paloan Hamlet; and is expected to be able to initiate the establishment of customary schools as part of the Tembawang conservation efforts.